2009
DOI: 10.1524/ract.2009.1569
|View full text |Cite
|
Sign up to set email alerts
|

Potential interferences on the pertechnetate-sulfide immobilization reaction

Abstract: Technetium-99 / Pertechnetate / Immobilization / Sulfide / InterferencesSummary. The potential interference from competing inorganic anions, chelating agents, and low molecular weight organic acids (LMWOAs), and the potential surface effects of selected minerals on the TcO 4 − -sulfide immobilization reaction (to form Tc 2 S 7 ) were investigated. The presence of the common inorganic anions, such as nitrate, studied did not affect the TcO 4 − -sulfide immobilization process even though their concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…To examine the influence of environmental conditions on the reductive immobilization reaction between TcO 4 and H 2 S, the effect of competing inorganic anions (nitrate), chelating agents (ethylenediaminetetraacetic acid, EDTA), low molecular weight organic acids, and surface effects of non-reducing minerals (goethite) were subsequently investigated (Liu et al, 2009). The presence of nitrate, EDTA and goethite did not affect the immobilization reaction, and the product was identified as Tc(IV) 2 S 7 in all cases by XANES and EXAFS.…”
Section: Sulfides For Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the influence of environmental conditions on the reductive immobilization reaction between TcO 4 and H 2 S, the effect of competing inorganic anions (nitrate), chelating agents (ethylenediaminetetraacetic acid, EDTA), low molecular weight organic acids, and surface effects of non-reducing minerals (goethite) were subsequently investigated (Liu et al, 2009). The presence of nitrate, EDTA and goethite did not affect the immobilization reaction, and the product was identified as Tc(IV) 2 S 7 in all cases by XANES and EXAFS.…”
Section: Sulfides For Remediationmentioning
confidence: 99%
“…The presence of nitrate, EDTA and goethite did not affect the immobilization reaction, and the product was identified as Tc(IV) 2 S 7 in all cases by XANES and EXAFS. Only maleic acid and fumaric acid inhibited the immobilization process by forming anionic water-soluble complexes with TcO 4 - (Liu et al, 2009). Szecsody et al (2014) found that alkaline and acidic waste streams had an impact on Hanford sediments and that the waste composition significantly altered contaminant speciation and mineralogy.…”
Section: Sulfides For Remediationmentioning
confidence: 99%
“…When dissolved in water, sodium sulfide, an ingredient of DuraLith, produces HS -, which promotes the formation of many metal sulfide precipitates. Liu et al (2008Liu et al ( , 2009 reported that the reaction between sulfide and TcO 4 in pH 9 aqueous solution under anaerobic conditions produces Tc 2 S 7 according to the reaction 2TcO 4 -+ 7HS -+ H 2 O → Tc 2 S 7 + 9OH -. Note that the sulfur in this compound is a mix of polysulfides such that each sulfur is not -2 charged.…”
Section: 9mentioning
confidence: 99%
“…Another approach employs Sn II incorporated into aluminophosphate nanocomposites for the reduction of TcO 4 – followed by stabilization within the nanocomposite , . Other approaches use sulfides or iron sulfides for reduction of TcO 4 – and subsequent sequestration of the resulting low valent Tc species …”
Section: Introductionmentioning
confidence: 99%